Corporealities in Italian Studies. (2nd April 2020) - Duncan, Derek; Webb, Heather
ABSTRACT: This article illustrates the different shape that discourses of corporeality have taken within the discipline from a chronological perspective. The first section explores how critical frameworks relating to embodiment, performativity and affect expand premodern Italian studies beyond the limited patriarchal canon and better understand 'performances' of the Passion by late medieval and early modern women religious as a form of co-suffering that foregrounds embodiment as discourse and substitute for silenced female voices. This is followed by a detailed reflection on how modern understandings of biopolitics and its technologies, mass demo-graphic mobility, and contemporary discourses on race and gender effect a shift away from binary modes of categorisation and critical understandings of the body to produce alternative forms of knowledge and more complex understandings of the symbolic figuration of the body as an object of national concern.